(3TQM TYQ CHj GdYdGA GdeYQis - (3GHf Gd SOj GdHWdjehSis; (3GdHhUjQj , TQa GdOjf CHh YHO Gddg eMeO Hf SYjO Hf MeGO Hf YHO Gddg GdUfgGLj GdeYQj,J (B696 (3g` s
(3ChdgG (B:s
(3JHJOF HTQM GdHjJ (B: ( (3hdjJ GdYbhHI JMQjbg aUGQhG QeGOkG HgG Ch MLe jbhd (B: (3djJ GdYbGH ai GdbjGeI cGf JMQjbkG jQLY GdNdb Hg QeGOkG Ch MeekG s
(3BNQgG (B:s
(3jfJgi HTQM GdHjJ (B: (3hLFJ Hjejfi Edi eJYUH afGOGc QHfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B772s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdCOHs